Activities Based on Wiki Platform for Engineering Higher Education: Students' Point of View - Almeida Mello, Gláucia Nolasco de (Revista Ibero-Americana de Estudos em Educação, 2017)
The fast evolution of Information and Communication Technology (ICT) introduced a new generation of learners that have been adopted mobile devices and Web 2.0 technologies to get information and communicate. The Web 2.0-based tools, such as blogs, wikis, Facebook, Instagram, etc, offer huge possibilities for collaboration. In this way, the main purpose of this research was plan an activity on wiki platform for Reinforced Concrete discipline in Civil Engineering course and answer the questions: (1) How should collaboration be effectively measured on wiki platform? (2) What is the students' point of view about using wiki platform for a collaboration activity? Wikispaces Classroom platform was chosen for the project because it is a free social writing platform, suitable for collaborative learning. Furthermore it works on modern browsers, tablets, and smart phone. A total of 167 students of Civil Engineering course were monitored on Wikispaces® platform. All students’ actions were analyzed and classified as low, medium or high level of collaboration. At the end of the project 111 students answered a questionnaire and 10 students participated of an informal interview where they expressed their opinion about the platform, the activities and the relationship with online peers. A descriptive statistical analysis of the data collected from the platform and the questionnaires answered by the students was performed. The results indicated that wiki platform is an important way to develop innovative activities and tasks for the purpose of to improve skills of engineering students such as: writing communication, organization, collaboration and critical thinking.